Germline Mutations in CIDEB and Protection against Liver Disease - Verweij, Niek; Haas, Mary E.; Nielsen, Jonas B.; Sosina, Olukayode A.; Kim, Minhee; Akbari, Parsa; De, Tanima; Hindy, George; Bovijn, Jonas; Persaud, Trikaldarshi; Miloscio, Lawrence; Germino, Mary; et al. (The New England journal of medicine, 2022)
Exome sequencing in hundreds of thousands of persons may enable the identification of rare protein-coding genetic variants associated with protection from human diseases like liver cirrhosis, providing a strategy for the discovery of new therapeutic targets. We performed a multistage exome sequencing and genetic association analysis to identify genes in which rare protein-coding variants were associated with liver phenotypes. We conducted in vitro experiments to further characterize associations. The multistage analysis involved 542,904 persons with available data on liver aminotransferase levels, 24,944 patients with various types of liver disease, and 490,636 controls without liver disease. We found that rare coding variants in , , , and were associated with increased aminotransferase levels and an increased risk of liver disease. We also found that variants in , which encodes a structural protein found in hepatic lipid droplets, had a protective effect. The burden of rare predicted loss-of-function variants plus missense variants in (combined carrier frequency, 0.7%) was associated with decreased alanine aminotransferase levels (beta per allele, -1.24 U per liter; 95% confidence interval [CI], -1.66 to -0.83; P = 4.8×10 ) and with 33% lower odds of liver disease of any cause (odds ratio per allele, 0.67; 95% CI, 0.57 to 0.79; P = 9.9×10 ). Rare coding variants in were associated with a decreased risk of liver disease across different underlying causes and different degrees of severity, including cirrhosis of any cause (odds ratio per allele, 0.50; 95% CI, 0.36 to 0.70). Among 3599 patients who had undergone bariatric surgery, rare coding variants in were associated with a decreased nonalcoholic fatty liver disease activity score (beta per allele in score units, -0.98; 95% CI, -1.54 to -0.41 [scores range from 0 to 8, with higher scores indicating more severe disease]). In human hepatoma cell lines challenged with oleate, small interfering RNA knockdown prevented the buildup of large lipid droplets. Rare germline mutations in conferred substantial protection from liver disease. (Funded by Regeneron Pharmaceuticals.).